PENINGKATAN HASIL BELAJAR MELALUI PEMBELAJARAN KONTEKSTUAL PKn KELAS III SD NEGERI 01 MANDOR - Susilowati, Susilowati; Marzuki, Marzuki; Sabri, Tahmid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractThe problem in this study is "What with Contextual Learning in Civics can improve the learning outcomes sisawa class III SDN 01 Mandor?". This study aims to know and learn about "Improved Learning Outcomes Through Contextual Learning in Civics Class III Primary School 01 Mandor. This research is a classroom action research and is collaborative. The place of research took place at the State Elementary School 01 Mandor with the subject of research that is the students of class III which amounted to 20 people. Technique of collecting data that is used is direct observation technique with data collecting tool that is IPKG I and IPKG II sheets. This research is done for 3 cycles. The results of the design of learning implementation plan obtained on average in the first cycle of 2.75, the cycle II of 3.60, the third cycle of 3.96, The results of learning learning obtained on average in the first cycle of 2.75, cycle II of 3.61, cycle III of 3.96, The results of the results of student learning results obtained on average in the first cycle of 61.00, cycle II of 72.00, the third cycle of 92.50. Total number of students in cycle I reached 15 people then there was an increase in cycle II reached 17 people and on the third cycle increased for all students class III which amounted to 20 people. From the data obtained can be concluded that there is an increase in each cycle. Thus research through contextual learning can improve the learning outcomes of Civic Education class III State Elementary School 01 Mandor.Â Keywords: Improvement, Learning Outcome, Civic Education, Contextual Learning.Â